Composite MWCNT/ MIL-101 (Cr)/CaCl2 as High-Capacity Water Adsorbent for Long-Term Thermal Energy Storage - Lou, Lanting; Xu, Min; Huai, Xiulan; Huang, Caifeng; Liu, Zhangli (Frontiers in Materials, 2021)
Mil-101 (Cr) material is considered to be one of the most potential thermochemical energy storage materials in recent years. It has the advantages of typical S-type water adsorption isotherm. Has low working temperature and large water adsorption amount. However, the adsorption properties of the material need to be improved under low water pressure. In order to improve the performance, the acidified MWCNTs were added before the hydrothermal reaction of mil-101 (Cr) materials to optimize the micro pore structure. After the preparation, the new composite thermochemical energy storage materials were prepared by impregnation with a certain concentration of calcium chloride aqueous solution. The effects of multi walled carbon nanotubes and calcium chloride on the physical and chemical properties of the materials were discussed. Through X-ray diffraction experiment, scanning electron microscope, microstructure analysis, nitrogen adsorption capacity test, water adsorption capacity test and other means, the micro characteristics, pore structure, crystal morphology and chemical composition of the materials were characterized, and the water adsorption performance of the materials was synthesized. The experimental results show that the addition of carbon nanotubes can improve the pore properties of the materials, so that the porous organic skeleton can accommodate more calcium chloride particles. The composite materials with calcium chloride can provide excellent hydrophilicity and high water adsorption capacity. In addition, the water adsorption rate and adsorption desorption cycle capacity of the material have been significantly improved. The experimental results show that when the mass fraction of calcium chloride reaches 30%, when 90mg acidified MWCNTs are added into every four chromium nitrate crystals, the hydrophilicity and adsorption capacity of the composite can reach a high equilibrium state. At the same time, the experimental yield of the material is high, the product is easy to obtain, the environmental friendliness is also reflected, so it is expected to become the adsorption heat pump thermochemical energy storage material with research potential.